THE INFLUENCE OF TIKTOK FOOD VLOGGER FARIDA NURHAN'S CONTENT TO ATTRACT CONSUMER INTEREST IN BUYING A FOOD PRODUCT - Ramadini, Amelia; Kholil, Syukur (Pena Cendekia Insani, 2025)
The rapid development of social media, especially TikTok, has changed the way people access information and decide to buy products, including food products. Farida Nurhan, as a popular food vlogger on TikTok, is considered to have a strong influence on consumer purchasing interest through her expressive communication style and interesting content. This study aims to analyze the influence of Farida Nurhan's content and the role of social media on consumer purchasing interest. The method used is a descriptive quantitative approach with a survey technique through an online questionnaire to 100 respondents aged 18–35 years. Data were analyzed using multiple linear regression. The results showed that both food vlogger content and the role of social media have a positive and significant influence on consumer purchasing interest, with a joint contribution of 43.3%. Farida Nurhan's content variable proved to be more dominant in influencing purchasing decisions. This finding strengthens the evidence that food vloggers act as effective persuasive communication agents in digital marketing. The practical implications of this study indicate that culinary industry players can utilize collaboration with food vloggers as a strategy to increase consumer visibility and purchasing interest in the digital era.